Grasping at sticks: pseudoneglect for perception but not action. - Hughes, L; Bates, T; Aimola Davies, A (2004)
A current question in theories of visual cognition is whether distinct cognitive processes subserve perceptual judgments and perception for action. This paper examines bisection tasks which have previously been used to demonstrate a dissociation between perception and action in brain injured patients. Forty neurologically intact participants completed a standard line bisection task and a variant of this task--rod bisection. A typical leftwards bias was observed for line bisection but when asked to locate the centre of wooden rods using perceptual judgments, a distinct rightwards bias was shown. By contrast, when participants were asked to pick the rods up by the centre, their judgments showed no bias. The results are in line with theories suggesting that perception and action are independent; however, alternative explanations are also considered.